2014
DOI: 10.1051/matecconf/20141304010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spur Gear Pair on Tooth Root Bending Stress in Radial Misalignment Contact Condition

Abstract: Abstract. This paper evaluates the effects of radial misalignment contact on the tooth root bending stress values of spur gear pair during the gear meshing cycle. Radial misalignment (H) is denoted as the deviation of the pinion nominal position with respect to the gear tooth along the pinion axis to the gear which happened from manufacturing assembly errors (AE). A model based on involute 3D parametric CAD geometry, of spur gear design ISO 6336:2006 is analysed with allowable AE values from minimum 10µm to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…It can be seen from Figure 5 that the stress in the middle part of gear width is always larger than that on the gear end. Similar simulation study was also reported in Lias et al 22 and Li. 23 It should be noticed that when the strain is measured along tooth width direction, the equivalent strain along the tooth height direction or circumferential direction must be computed based on Poisson's coefficient and may not be a trivial task.…”
Section: Sensor Deployment Specificssupporting
confidence: 90%
“…It can be seen from Figure 5 that the stress in the middle part of gear width is always larger than that on the gear end. Similar simulation study was also reported in Lias et al 22 and Li. 23 It should be noticed that when the strain is measured along tooth width direction, the equivalent strain along the tooth height direction or circumferential direction must be computed based on Poisson's coefficient and may not be a trivial task.…”
Section: Sensor Deployment Specificssupporting
confidence: 90%